Exercise response to real combat in elite taekwondo athletes before and after competition rule changes - Janowski, M.; Zielinski, J.; Kusy, K. (The Journal of Strength and Conditioning Research, 2021)
We hypothesize that recent (2017) changes in competition rules significantly affected kinematic (mechanical activity) and physiological (cardiopulmonary indices and lactate concentration) profile of the taekwondo combat, which is currently becoming more demanding in terms of exercise intensity and fatigue. Twenty two male and female elite taekwondo athletes were followed up for over 2 years. In total, 258 real tournament combats were included in the analysis (133 in old rules and 125 in new rules). Kinematic and physiological characteristics were recorded using a biomonitor (BioHarness 3; Zephyr Technologies) worn by athletes during tournaments. Blood samples were drawn after each combat for lactate concentration. Our research showed that recent amendments of competition rules were linked to a noticeable shift toward higher kinematic output and, consequently, increased physiological response. Significant increments in kinematic variables (3-8%), heart rate (HR) (1.5-1.8%), energy expenditure (EE) (3-5%), overall physiological load (2-4%), and lactate concentration (~15% immediately after exercise and ~25% in recovery) suggest that new rules are more demanding, although the statistical effect size is only small or moderate. In conclusion, after competition rule changes, there has been a shift in taekwondo combat profile toward greater body movement dynamics, higher intensity, and greater postexercise fatigue. The values of key indices of exercise response (mechanical activity, HR, EE, and lactate concentration) during tournaments are near or exceeding the maximum attained during progressive exercise until exhaustion. Therefore, more focus is needed on taekwondo-specific high-intensity training and postcombat recovery to adapt athletes to increased competition requirements.